Analysis of traffic accident rates during the Covid-19 pandemic in Gorontalo City - Mahendra, Edwin Isa; Igirisa, Shendy Septiani; Ahmad, Adam (International Journal for Educational and Vocational Studies, 2021)
Traffic accidents are something that everyone wants to avoid but sometimes there are still many traffic accidents that suddenly occur caused by poor road infrastructure or the negligence of each road user himself. The data used in this study is the number of the accident in 2018-2021 based on the number of accidents and the number of human victims (FK, SI, MI). The results of the analysis of the traffic accident rate show that the number of accidents in 2018 was 108 events with a percentage of 27%, in 2019 there were 158 events with a percentage of 39%, in 2020 there were 87 events with a percentage of 21% and in 2021 there were 55 events with a percentage of 13%. The most traffic accidents occurred in 2019 with the number of victims who died were 19 victims with a percentage of 11%, victims who suffered serious injuries as many as 1 with a percentage of the situation was 5% and victims who suffered minor injuries were 157 victims with a percentage of 88%. Whereas in 2020 the number of traffic accidents decreased with a total of 121 victims with the percentage of FK victims being 13%, SI victims being 3% and MI victims being 84%.